Proceedings of the Seventh ACM SIGKDD International Conference on Knowledge Discovery and Data Mining 2001
DOI: 10.1145/502512.502546
|View full text |Cite
|
Sign up to set email alerts
|

Random projection in dimensionality reduction

Abstract: Random projections have recently emerged as a powerful method for dimensionality reduction. Theoretical results indicate that the method preserves distances quite nicely; however, empirical results are sparse. We present experimental results on using random projection as a dimensionality reduction tool in a number of cases, where the high dimensionality of the data would otherwise lead to burdensome computations. Our application areas are the processing of both noisy and noiseless images, and information retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
722
1
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,069 publications
(736 citation statements)
references
References 28 publications
5
722
1
8
Order By: Relevance
“…In contrast, our algorithm does not suffer from the problems with online self-taught learning approaches [24] as the proposed model with the measurement matrix is data-independent. It has been shown that for image and text applications, favorable results can be achieved by methods with random projection than principal component analysis [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, our algorithm does not suffer from the problems with online self-taught learning approaches [24] as the proposed model with the measurement matrix is data-independent. It has been shown that for image and text applications, favorable results can be achieved by methods with random projection than principal component analysis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Given 0 < < 1 as well as β > 0, and let R ∈ R n×m be a random matrix projecting data from R m to R n , the theoretical bound for the dimension n that satisfies the Johnson-Lindenstrauss lemma is n ≥ 4+2β 2 /2− 3 /3 ln(d) [16]. In practice, Bingham and Mannila [25] pointed out that this bound is much higher than that suffices to achieve good results on image and text data. In their applications, the lower bound for n when = 0.2 is 1600 but n = 50 is sufficient to generate good results.…”
Section: Discussionmentioning
confidence: 99%
“…In order to generate a single summary vector per shot, the vectors from each feature modality are concatenated, resulting in an even larger vector. Since the spill tree requires a low dimensional representation, the shot vectors are reduced to 100 dimensions by random projection [3]. Random projection is simple, fast, and is known to preserve neighborhood structure [8] making it a good choice for preprocessing nearest neighbor data.…”
Section: Nearest Neighbor For Scalabilitymentioning
confidence: 99%
“…When the number of variables is large, the visualisation may combine a preprocessing stage by selection or linear transformation [3,4,5]. In a co-clustering method, both sides of the matrix are partionned [6], hence the reduction of the variables space and the row clustering occur simultaneously.…”
Section: Introductionmentioning
confidence: 99%